„La Țigănci”, nuvela-parabolă a profetismului eliadesc / "La Țigănci" – The Parable of the Eliadesc Prophetism - Danciu, Liliana (Swedish Journal of Romanian Studies, 2018)
The unprecedented experience of Gavrilescu, the main character in the La Țigănci short story, continues to arise various interpretations, proving the viability of this eliadesc writing. For some literary critics, he is the anti-hero by definition, which lives what Eliade understands by "level break", but without understanding anything of it. The ordinary man, with a banal existence, routinely in the profane becomes the Chosen One uselessly claimed by sacred, for ignorance prevents him from seeing beyond the Illusion. In the hut of the gypsies, he crosses a rite of passage, from life to death, proof being the shrouded curtain that will wrap his naked body, the terrible thirst for unpopularity, and the surprising encounter with the always young Hildegard, the beloved of his youth. In this article, I try to reveal another dimension of this eliadesc short story, linked to the name of the main character, which, in my opinion, refers to the name of the archangel Gabriel, the "pair" of the other, Michael. As it is known, the name of the archangel Michael is directly related to the Romanian legionary movement in the inter-war period, a nationalistic, violent and criminal political-ideological movement that has successfully manipulated local religious and cultural elements to gain followers and become strong. Up to a point, the Romanian legionary movement stood under the sign of both archangels, synthesizing both the intellectual and the political dimensions. In time, the two directions have broken apart, and the legion has remained exclusively under the warlike sign of the warrior archangel. The Romanian intellectuals, who originally sympathized with the nationalist ideals of the legionary movement, distanced themselves from it and remained under the soteriological mark of Archangel Gabriel. This is, in my opinion, the message hidden by Eliade in this unusual short story. Also, using allegory and symbol, the Romanian author turns out to be a man of vision and prophesies the future of Romania, which has been culturally and historically marked, in time, by Germany. The present does not contradict Eliade, because Germany is the engine of the European Union, of which Romania wants to be part.